Uso de filtros de carvão ativado granular associado a microrganismos para remoção de fármacos no tratamento de água de abastecimento - Borges, Rívea Medri [UNESP]; Minillo, Alessandro [UNESP]; Lemos, Eliana Gertrudes de Macedo [UNESP]; do Prado, Heloiza Ferreira Alves [UNESP]; Tangerino, Edson Pereira [UNESP] (FapUNIFESP (SciELO), 2016)
The way of life of modern societies has originated the daily intake of pharmaceuticals and numerous other molecules of continuous use in aquatic environments, emerging compounds that brings potential risk for human health mainly due to exposure resulted from the inevitable contamination of sources of drinking water supply and its transference to the water treatment plants (WTP) where they are not removed. The use of granular activated carbon in filters proves to be a viable option for WTP, but satisfactory efficiency requires periodic regeneration of the material, burdening the treatment costs. However, it is noted that under low filtration rates, the natural colonization of filters by microorganisms — biofilm formation — may be an alternative for increasing the lifetime of carbon, as well as to decompose these complex molecules into assimilable mineral elements, thereby reintroducing them to the natural biogeochemical cycles. This study evaluated the activated carbon with biofilm as the filter media, during 24 weeks, under laboratory conditions, considering the removal of the pharmaceuticals diclofenac sodium, ibuprofen, naproxen and amoxicillin; experienced under batch system the potential of the microorganisms adhering to the filters in degrade the tested drugs, as well as phylogenetically identified the predominant microorganisms in biodegradation. The results show drug removal over 80%. It was observed the presence of the bacteria genus Bacillus, Burkholderia, Cupriavidus, Pseudomonas, Shinella and Sphingomonas. This study allows us to infer the capacity to remove pharmaceuticals by the bacteria present in the activated carbon filters, and the possible use of this technology as an alternative for control and removal of these substances in drinking water treatment.
Use of granular activated carbon filters associated with microorganisms to remove pharmaceuticals in drinking water treatment
Keywords: Biofilm; Drinking water treatment; Emerging contaminants; Granular activated carbon; Pharmaceuticals removal